A THE EFFECT OF FINANCIAL LITERACY, TECHNOLOGY LITERACY, AND LYFESTYLE ON THE USE OF ELECTRONIC MONEY (CASE STUDY OF ISLAMIC BANKING STUDENTS IN JAKARTA) - Mitra Sami Gultom; Ainul Latif (Universitas Muhammadiyah Prof Dr Hamka, 2022)
The current study aims to determine the effect of financial literacy, technology literacy, and lifestyle on the use of electronic money on Islamic Banking students. The type of this study is a quantitative approach using a descriptive technique. The method used in the study was distributing questionnaires to 91 students who enroll Islamic Banking course in Jakarta who use electronic money. Further, non-probability sampling and purposive sampling methods were applied to yield the data. Processing the data were then calculated by SPSS 25 and Microsoft Excel. The data analysis utilized a Multiple Linear Regression Analysis. The results of this study indicate that financial literacy, technological literacy and lifestyle simultaneously have positive and significant effects on the use of electronic money. The partial test shows that the financial literacy variable (X1) does not have a significant effect on the use of electronic money (Y), while the technological literacy variable (X2) has a positive and significant effect on the use of electronic money (Y), and the lifestyle variable (X3) has a positive effect and significant to the use of electronic money (Y). Keywords: Financial Literacy, Technology Literacy, Lifestyle, Electronic Money.